PENCABUTAN DINI GIGI SULUNG AKIBAT CARIES GIGI DAPAT MENYEBABKAN GIGI CROWDING - Ni Luh Putu Suarniti (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
Primary teeth are the teeth while the children who will be replaced by permanent teeth. By a variety  of  causes,  primary  teeth  are  not  able  to  function  so  that  the necessary  action  is  premature  retraction. Early lifting of deciduous teeth caused by many factors, some of them by  dental caries. The prevention can be done to maintain the baby teeth are Topical Fluoride Application, Fissure Sealant, and Orthodontic Interceptive. Although temporary, the child's primary teeth also require treatment, such as tooth extraction eldest, eldest dental fillings, and root canal treatment in primary teeth. These things are done to avoid the occurrence of dental crowding or over‐crowded teeth.